Ten Years of Boko Haram in Nigeria The Dynamics and Counterinsurgency Challenges - Omenma, J. Tochukwu; Onyishi, Ike E.; Okolie, Aloysius-Michaels. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book provides a contemporary overview of Boko Haram's activities. Since Boko Haram emerged in 2002, media-driven narratives as well as social scientific methodologies have been increasingly applied to draw generalisable conclusions on what goals the groups have pursued, what strategies it has used for these purposes and the counter campaign strategies authorities have pursued. But from 2009 to 2018, Boko Haram has pursued high-intensity violence: assassinations, bombing, kidnappings, beheading or threats of violence, conscriptions and territorial occupation. This makes it imperative to deepen and broaden our understanding of the groups' activities toward a problem-solving and policy-relevant analysis. Previously published in Security Journal Volume 33, issue 3, September 2020.
1. A decade of Boko Haram activities: the attacks, responses and challenges ahead - J. Tochukwu Omenma, Ike E. Onyishi and Alyious-Michaels Okolie -- 2. A decade of terror: revisiting Nigeria's interminable Boko Haram insurgency - Olumuyiwa Babatunde Amao -- 3. Boko Haram insurgency: a decade of dynamic evolution and struggle for a caliphate - J. Tochukwu Omenma -- 4. Counterinsurgency operations of the Nigerian military and Boko Haram insurgency: expounding the viscid manacle - Freedom C. Onuoha, Chikodiri Nwangwu and Michael I. Ugwueze -- 5. Mathematical approach to the analysis of terrorism dynamics - C. Okoye, O. C. Collins and G. C. E. Mbah -- 6. Boko Haram, pro-synergic conditions and community involvement in counterinsurgency - Bonaventure N. Nwokeoma, Kelechi E. Okpara and Nnabuike O. Osadebe -- 7. Interagency collaboration and the management of counter-insurgency campaigns against Boko Haram in Nigeria - Okechukwu M. Ikeanyibe, Charles N. Olise, Isah Abdulrouf and Ikechukwu Emeh -- 8. Non-military approach against terrorism in Nigeria: deradicalization strategies and challenges in countering Boko Haram - Hakeem Onapajo and Kemal Ozden -- 9. Responsibility to protect: external intervention on Boko Haram terrorism in Nigeria - Chijioke Egwu Ekumaoko and Kingsley Emeka Ezemenaka. .
Keywords: Africa -- History; Terrorism; Political violence; Africa, Sub-Saharan -- History; World politics; African History; Terrorism and Political Violence; History of Sub-Saharan Africa; Political History